A 'Homeland's' Harvest: Biotraffic and Biotrade in the Contemporary Ciskei Region of South Africa. Issue 3 (4th May 2019) - Morris, Christopher
Abstract : What, scholars of South Africa have recently asked, has become of the former 'homelands'? This article describes the significance of the former Ciskei homeland to a multi-million-dollar supply chain linking rural South African plant harvesters with multinational pharmaceutical companies. The former Ciskei is a primary extraction site for the medicinal plant Pelargonium sidoides, which generates tens of millions of dollars in annual sales as an internationally marketed pharmaceutical product. Drawing upon 15 months' fieldwork in South Africa conducted between 2009 and 2018, I show how dynamics associated with the homeland past and more recent governance policies – dynamics such as still active homeland-era laws, labour conditions, concentrations of people and livestock, industry middlemen and traditional leaders – all shape a contemporary and lucrative industry. The former Ciskei is more than a marginal space from which migrant workers continue to seek access to South Africa's 'formal business sectors'. The region is a crucial link in a system of transnational accumulation initiated within its enduring borders.